Legal and Psychological Impact of Child Sexual Harassment: Dampak Hukum dan Psikologis Pelecehan Seksual terhadap Anak - Astuti, Fitriani Dwi; Samian, Samian; Suharto, Achmad; Tufiqurrohman, A.H. As’ari; Wibowo, Dwi Edi (Indonesian Journal of Law and Economics Review, 2024)
Background: Sexual harassment against children in Pekalongan City has escalated, with factors such as diminished parental supervision and shifting moral values contributing to its prevalence. Knowledge Gap: Existing literature primarily explores legal repercussions and short-term psychological impacts, leaving a gap in comprehensive studies on long-term emotional effects and effective legal protection measures. Aims: This study aims to fill these gaps by identifying causative factors, evaluating psychological and emotional impacts over time, and assessing current legal protections. Results: The research highlights that children experiencing sexual abuse face severe psychological conditions like anxiety and depression, along with lasting emotional disturbances such as trauma and emotional dysregulation. Legal efforts are currently centered on reactive measures rather than preventative strategies. Novelty: This study is novel in its longitudinal analysis of emotional impacts and its critique of legal frameworks in place, suggesting improvements for future protective measures. Implications: The findings advocate for enhanced legal frameworks that focus not only on punitive measures but also on preventive and rehabilitative strategies to better protect children and foster resilience against the psychological and emotional scars of abuse. Highlights: Causative Factors: Key contributors include decreased parental supervision and shifting societal values. Long-term Impacts: Highlights severe psychological effects like depression and trauma. Legal Frameworks: Stresses the need for improved preventive and rehabilitative legal measures. Keywords: Children, Sexual Abuse, Legal Protection